Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden (Swedish Winter Sports Research Centre at Mid Sweden University, 2022)
The conference was a mixture of keynote presentations, poster / oral presentations and seminars. With that said, one key element and focus of the conference was to provide a more holistic view of sports perfor mance and health. It is often easy to think that performance comes down to just a few factors, but in reality, it is way more complex. The mission with NWSC is to appeal scientists, coaches and athletes to contribute to this puzzle and also shed light on collaborations between various sciences. The conference covered a wide range of topics including training sciences, coaching, the female athlete, social science, exercise physiology, performance analysis and biomechanics.